Changes in therapeutic options for hepatocellular carcinoma in Asia. (29th November 2021) - Ogasawara, Sadahisa; Koroki, Keisuke; Kanzaki, Hiroaki; Kobayashi, Kazufumi; Kiyono, Soichiro; Nakamura, Masato; Kanogawa, Naoya; Saito, Tomoko; Kondo, Takayuki; Nakagawa, Ryo; Nakamoto, Shingo; Muroyama, Ryosuke; et al.
Abstract: The incidence rate of hepatocellular carcinoma (HCC) is expected to increase, with most cases occurring in Asia. In some parts of Asia, the occurrence of HCC developing from metabolic‐related liver disease has markedly increased in recent years, whereas the occurrence of HCC developing from viral‐hepatitis–related liver disease has decreased. Advancements in the treatment of HCC over the past few decades has been remarkable, with most treatment strategies to remove or control liver tumours (hepatic resection, local ablation, radiation therapy, transarterial chemoembolisation, hepatic arterial infusion chemotherapy) primarily developing in Asia. In addition, recent progress in systemic therapies has prolonged the prognosis of advanced HCC. Nowadays, six regimens of systemic therapies have become available in most countries, according to phase III trials (atezolizumab plus bevacizumab, sorafenib, lenvatinib, regorafenib, cabozantinib and ramucirumab). In a global randomised phase III trial (IMbrave 150 trial), the most effective of the latest drug designs was newly emerged combination immunotherapy (atezolizumab plus bevacizumab), which has shown significantly prolonged overall survival compared with sorafenib, which was the first‐line systemic therapy for more than a decade. Now, the treatment dynamics for HCC are undergoing a major transition as a result of two important changes: the replacement of viral‐related HCC by metabolic‐related HCC and the emergence of combination immune therapy.